The Concept of Patriotism and National Consciousness in the Thought of Stanislaw Ossowski - Brzechczyn, Krzysztof (Sensus Historiae, 2024)
The aim of the paper is the interpretation of Stanisław Ossowski’s concept of patriotism and national consciousness. In the first part, biographical information is presented. In the second part, Ossowski’s vision of patriotism is analyzed. In the third part, I present Ossowski’s concept of national consciousness that implicates his notion of nation. His main distinction is the differentiation between private and ideological homeland. The first one is a place where a given person was born and raised. The basis of belonging to an ideological homeland is an individual’s conviction about his/her participation in the community that has a common homeland consisting of culture, language, history, ideals, and values.